Prospects for Anti-Biofilm Pharmaceuticals - Philip S. Stewart (MDPI AG, 2015)
This commentary highlights several avenues currently being pursued in research labs to the development of new anti-biofilm pharmaceuticals. There is a real need for alternative therapeutic modalities for treating the persistent infections that sometimes form on implanted medical devices or compromised niches within the body. Strategies being researched include discovering new antimicrobial agents that kill microorganisms in biofilms more effectively than do existing antibiotics, designing drugs that block microbial adhesion or interfere with intercellular communication, developing chemistries to disperse biofilms, and combining agents with different mechanisms of action. Though the need is great, the pathway to commercialization of new drugs is steep. One possible streamlined approach to navigating the regulatory approval process is to repurpose old drugs, a strategy that a few groups have shown can yield agents with anti-biofilm properties.